1991
DOI: 10.1055/s-2007-1024698
|View full text |Cite
|
Sign up to set email alerts
|

Ventilatory Threshold and Maximal Oxygen Uptake during Cycling and Running in Female Triathletes

Abstract: Maximal oxygen uptake (VO2max) and the ventilatory threshold (Tvent) were measured during cycle ergometry (CE) and treadmill running (TR) in a group of 10 highly trained female triathletes. Tvent was defined as the VO2 at which the ventilatory equivalent for oxygen increased without a marked rise in the ventilatory equivalent for carbon dioxide. Female triathletes achieved a significantly higher mean (+/- SE) relative VO2max for running (63.6 +/- 1.2 ml.kg-1.min-1) than for cycling (59.9 +/- 1.3 ml.kg-1.min-1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
40
6
7

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 14 publications
13
40
6
7
Order By: Relevance
“…These values are in well accordance with values of other elite triathletes around the world and higher than ironman triathletes (Schneider, 1990). Additionally, we checked the hypothesis that absolute values of VO2max are typically higher in men than in women.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…These values are in well accordance with values of other elite triathletes around the world and higher than ironman triathletes (Schneider, 1990). Additionally, we checked the hypothesis that absolute values of VO2max are typically higher in men than in women.…”
Section: Resultssupporting
confidence: 71%
“…However, the degree of trainability affects VO2max widely; for example, conditioning may double VO2max in some individuals, and will never improve it at all in others (Bouchard, 1999). Also it has been shown that respiratory muscle training does not improve VO2max of triathletes and marathon runners Authors also speculate that triathlon training results in general adaptations which enhance maximal oxygen uptake values, whereas anaerobic threshold adaptations occur primarily in the specific muscle groups utilized in training (Schneider, 1991). Additionally, it has been suggested that the exercise testing mode affects the VO2max (Roels, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The SPT athletes had relative _ V O 2 peak values of approximately 47 mLÁkg -1 Ámin -1 , slightly higher than those previously reported for age-matched subjects who were not specifically trained (i.e., 41-45 mLÁkg -1 Ámin -1 ; Jones and Carter 2004;Koppo et al 2004a), but somewhat lower than those reported previously by Fukuoka et al (1995) for American football players (53 mLÁkg -1 Ámin -1 ) and by Granier et al (1995) for track sprint runners (52 mLÁkg -1 Ámin -1 ). The % _ V O 2 peak at the estimated LT was lower in both our SPT and ENT athletes than has been reported in earlier studies (Schneider et al 1990;Fukuoka et al 1995). The cause of these differences is not clear, but they might be related to differences in the protocols and procedures used for the measurement of _ V O 2 peak or estimation of LT, or to differences in the relative training status of the subjects.…”
Section: Discussioncontrasting
confidence: 52%
“…and disease have reported that the V O 2 at the anaerobic (AT) or ventilatory (T vent ) threshold is significantly higher when incremental exercise testing is performed on a treadmill than on a cycle ergometer [9,12,15,18,19,23,25,30,32,43]. These Relationship between exercise-induced decreases (Δ) in plasma bicarbonate (HCO 3 -) concentrations and increases in the ventilation above and beyond that needed to support any given increment in oxygen uptake (i.e., excess ventilation) during submaximal and maximal exercise on a cycle ergometer and treadmill.…”
Section: 32b Ventilatory (Anaerobic) Threshold Numerous Studies mentioning
confidence: 99%